Growth of high-quality GaN nanowires on p-Si (1 1 1) and their performance in solid state heterojunction solar cells. (October 2021) - Saron, K.M.A.; Ibrahim, M.; Taha, T.A.; Aljameel, A.I.; Alharbi, Abdullah G.; Alenad, Asma M.; Alshammari, Basheer A.; Almutairi, Ghzzai N.; Allam, Nageh K.
Highlights: Optimized CVD growth of catalyst-free GaN nanowires (NWs)/p-Si heterojunctions. NH3 gas flow rate determined the morphology, crystal structure, and composition. Raman and XRD analyses revealed lower internal stress in the prepared NWs. The η of the devices varies with the NH3 flow rate used in the synthesis of GaN NWs. The n-GaN NWs/p-Si solar cells revealed a maximum η of ∼7.87%. Abstract: We report on the optimized growth of catalyst-free GaN nanowires (NWs)/p-Si by the vapor–solid (V-S) method using chemical vapor deposition (CVD). The effect of NH3 gas flow rate on the morphology and photovoltaic behavior of the material has been investigated. The length and the diameter of the NWs decrease as the NH3 flow rate increases. Raman and X-ray diffraction (XRD) analyses reveal lower internal stress in the prepared NWs. The photoluminescence (PL) spectra indicate strong near band-edge (NBE) peaks extending from 365 to 368 nm and their intensity varied significantly with the NH3 flow rate. The assembled n-GaN NWs/p-Si solar cell devices reveal a maximum conversion efficiency of ∼7.87% under AM 1.5G illumination. This study shows that the morphology, optical, and performance of the fabricated n-GaN NWs on p-Si are strongly affected by the gas flow rate.